Soviet Intellectuals and Political Power : The Post-Stalin Era - Shlapentokh, Vladimir (Book collections on Project MUSE., 2014)
In this unprecedented work on the status and role of intellectuals in Soviet political life, a former Soviet sociologist maps out the delicate, often paradoxical, ties between the political regime and the creative thinkers who play a major part in the movement toward modernization. Beginning with Stalin, Vladimir Shlapentokh explores the mutual need and antagonism that have existed between political leaders and intellectuals. What emerges is a fascinating portrayal of the Soviet intellectual network since the 1950s, which touches on such topics as the role of literature and film in politica.